Reprodukovatelnost výsledků testů kontrastové citlivosti - Langrová, H; Hejcmanová, D; Peregrin, J (Ceska a slovenska oftalmologie, 1996)
Two methods (a double staircase and an adjustment method) for repeated measuring of the contrast sensitivity in inexperienced observers (e.g. in patients undergoing the photorefractive keratectomy) were compared in 10 subjects. Using the coefficient of repeatability of Bland and Altmann it could be shown that the reproducibility is better in the method of adjustment. The coefficient of repeatability of this method amounted for 95% confidence limits to 4.78 dB, whereas in the method of double staircase it was 8.70 dB.
Keywords: zrakové testy; Male; Vision Tests; Adult; Aged; dospělí; mužské pohlaví; senioři; reprodukovatelnost výsledků; počítačové zpracování signálu; Reproducibility of Results; citlivost na kontrast; lidé; ženské pohlaví; Humans; Signal Processing, Computer-Assisted; Female; lidé středního věku; Middle Aged; Contrast Sensitivity